Fresno County Bar Association Witkin Luncheon at Hilton Hotel with Bernard Witkin - Watkins, Howard::::::::: (1987)
Judge Blaine Pettitt, Harold Thompson, Judge Robert Mardikian, Justice Donald Franson, Bernard Witkin, Presiding Justice George Brown and Judge James V. Paige